Retraction Notice: Molecular Cloning and Characterization of a Novel Transforming Growth Factor-β Homologue (TGH) Derived from Trichinella spiralis - Chaimon, Salisa; Adisakwattana, Poom; Chantree, Pathanin; Martviset, Pongsakorn (Asian Medical Journal and Alternative Medicine, 2022)
The article has been retracted at the request of the author.